Significado atribuído às relações "chegar antes de" e "não chegar depois de" por alunos do Ensino Médio - Martinelli, Luciane (2004)
This study aims to investigate if the students of High School, from a private school in São Bernardo Campo, atribute restricted significance to the relations arriving before and not arriving before and, in positive case, if the students of the 1 st grade from the same school can have these meanings amplified as a result of a process of didactic intervention. Firstly we applied a diagnosis and the achieved results led to the conclusion that the students of High School atribute restricted significance to the relations mentioned, in the resolution of problems. Secondly, we elaborated, for the students of the 1 st grade, a Didactic Engineering, using as theoretical reference the dialectic object-tool of Douady. Analysing the data we concluded that there was an evolution in the knowledge of the students which was a result of the process of the didactic intervention used in the research